Insect immunity: isolation from immune blood of the dipteran Phormia terranovae of two insect antibacterial peptides with sequence homology to rabbit lung macrophage bactericidal peptides. - Lambert, J (1989)
We have isolated from the hemolymph of immunized larvae of the dipteran insect Phormia terranovae two peptides that are selectively active against Gram-positive bacteria. They are positively charged peptides of 40 residues containing three intramolecular disulfide bridges and differ from one another by only a single amino acid. These peptides are neither functionally nor structurally related to any known insect immune response peptides but show significant homology to microbicidal cationic peptides from mammalian granulocytes (defensins). We propose the name "insect defensins" for these insect antibiotic peptides.